A new species of Ricinulei of the genus Cryptocellus Westwood (Arachnida) from northern Brazil - Tourinho, Ana Lúcia; Man-Hung, Nancy F. Lo; Bonaldo, Alexandre Bragio (Zootaxa, 2010)
Cryptocellus iaci sp. nov. is described from an adult female collected during a field campaign organized by the World Wildlife Fund to the median Negro River at the Jauaperí river, in the state of Roraima, northern Brazil.